Strategi Digital Marketing Melalui Pengelolaan Media Sosial @notapprovedyet oleh Content Marketing Shopee Indonesia - Khadijah Najma Zahirah; Sutisna Riyanto (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The rapid growth of digital technology has revolutionized marketing practices, with social media becoming a primary platform for brand communication and audience engagement. Shopee Indonesia, as one of the leading e-commerce platforms in Southeast Asia, leverages various social media channels to strengthen its brand presence and connect with consumers. This study examines Shopee's digital marketing strategy through the management of the @notapprovedyet social media account, which creatively promotes Shopee products based on current social trends. The main focus of this study is to explain the content creation process and analyze the performance of accounts on Instagram, TikTok, and YouTube managed by Shopee Indonesia's Content Marketing Division. Using a creative marketing approach, this study aims to provide insights into effective social media management. The research findings are expected to contribute to understanding how the right social media strategy can increase audience engagement and brand awareness, especially in the highly competitive e-commerce industry.